Bosnia and Herzegovina : Diagnostic Review of Consumer Protection in the Microfinance Sector - World Bank (World Bank, Washington, DC, 2017)
This 2012 microcredit sector diagnostic review complements the 2011 review of the Banking sector and analyses the following five areas of consumer protection in microcredit: i) existing institutional arrangements, ii) consumer disclosure; iii) business practices; iv) dispute resolution mechanisms; v) and financial education programs. Bosnia and Herzegovina was the largest microfinance market in Europe and Central Asia until the 2008 global crisis prompted a rapid reversal. Authorities identified consumer protection in microfinance as high priority and introduced new regulatory provisions to stabilize the sector. This review analyzes the existing consumer protection framework and offers recommendations for further improvements. The Institutional Arrangements section covers the agencies responsible for implementing consumer protection, as well as industry and consumer associations. The section on Consumer Disclosure focuses on standard formats for price and product comparison, disclosure provisions, and basic rights of consumers. The Business Practices section covers unfair or abusive practices, standard consumer contract provisions, and industry Code of Conduct. The section on Dispute Resolution focuses on internal complaints mechanisms in financial institutions and out-of-court mechanisms. The section on Financial Education focuses on measures aimed at increasing consumer financial literacy and awareness.